2010
DOI: 10.1021/nn100465s
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructural Transformation and Formation of Heterojunctions from Si Nanowires

Abstract: ecause of the importance of Si-based materials to the electronic industry, considerable effort has been devoted to studying Si and metal silicide nanowire structures. 1 Nickel silicides show low electrical resistivity and excellent thermal stability without the electron migration effect at high temperatures. They are promising candidates as the electrical contacts for Si nanowire devices because of their good compatibility with Si and small lattice mismatch at the interface. The conventional methods for fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Therefore, a preliminary growth mechanism for the nickel silicide nanostructures can be proposed. It has been well accepted that the temperature and the pressure of the reaction precursor are the key factors affecting the formation of metallic silicide [23][24][25][26]. In our synthesis, when the gas ratio of SiH 4 and H 2 is fixed at 80:80 (sccm), Ni 2 Si, Ni 3 Si 2 , and NiSi NWs are successfully synthesized at the temperature of 450, 500, and 600 8C, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…Therefore, a preliminary growth mechanism for the nickel silicide nanostructures can be proposed. It has been well accepted that the temperature and the pressure of the reaction precursor are the key factors affecting the formation of metallic silicide [23][24][25][26]. In our synthesis, when the gas ratio of SiH 4 and H 2 is fixed at 80:80 (sccm), Ni 2 Si, Ni 3 Si 2 , and NiSi NWs are successfully synthesized at the temperature of 450, 500, and 600 8C, respectively.…”
Section: Resultsmentioning
confidence: 86%
“…[273][274][275][276] Until around 2010, most of PEC cells focused on the solar cell application using redox electrolytes, such as HBr/Br 2 [277] and Fe(CN) 6 4− /Fe(CN) 6 3− . [278] To protect the surface of SiNWs, methylation, [279] carbon nanotubes, [280] and double-walled carbon nanotubes [281] have been applied. To enhance the cell performance, Pt nanoparticles have been decorated on SiNWs, [279,282] which leads to ≈8% of conversion efficiency.…”
Section: Photoelectrochemical Solar Cells and Photoelectrocatalysismentioning
confidence: 99%
“…[278] To protect the surface of SiNWs, methylation, [279] carbon nanotubes, [280] and double-walled carbon nanotubes [281] have been applied. To enhance the cell performance, Pt nanoparticles have been decorated on SiNWs, [279,282] which leads to ≈8% of conversion efficiency. To minimize the photocorrosion of SiNW in aqueous electrolytes, ionic liquid has also been used as electrolyte, which has yielded long-term stability.…”
Section: Photoelectrochemical Solar Cells and Photoelectrocatalysismentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] The epitaxial layer-by-layer growth of CoSi 2 along the Si NW axis was observed, which was explained by the limited supply of Co atoms due to point contact. 12 In that report, it was found that having a lower interface energy between the native oxide and Si than between native oxide and silicide prevented heterogeneous nucleation, resulting in homogeneous nucleation.…”
mentioning
confidence: 99%